circFOXM1 contributes to sorafenib resistance of hepatocellular carcinoma cells by regulating MECP2 via miR-1324 - Hanqin Weng; Lexiang Zeng; Linhui Cao; Tao Chen; Yanshan Li; Yunxiuxiu Xu; Yaorong Peng; Yibiao Ye (Elsevier, 2021)
As one of the most common malignant tumors, hepatocellular carcinoma (HCC) is a leading cause of cancer-related deaths around the world. Emerging studies have indicated that circular RNAs (circRNAs), which play a crucial role in HCC pathogenesis and metastasis, are differentially expressed in HCC. However, the regulatory mechanisms of circRNA on sorafenib resistance of HCC are still unknown. In our study, we identified a novel circRNA, circFOXM1, using RNA sequencing (RNA-seq) that was increased in sorafenib-resistant HCC tissues. Functionally, circFOXM1 significantly inhibited HCC growth and enhanced sorafenib toxicity in vitro. Mechanistically, circFOXM1 acted as a sponge of microRNA (miR)-1324, which is a negative regulator of MECP2, indicating that circFOXM1 downregulation would regulate sorafenib resistance of HCC via releasing more free miR-1324 and suppressing MECP2 expression. Furthermore, miR-1324 overexpression was capable of reversing the circFOXM1-induced malignant phenotypes and elevated expression of MECP2 in HCC cells. circFOXM1 partially contributed to sorafenib resistance of HCC cells through upregulating MECP2 expression by sponging miR-1324.